0.1–1-THz High-Repetition-Rate Femtosecond Pulse Generation From Quasi-CW Dual-Pumped All-Fiber Phase-Locked Kerr Combs - Zhengqian Luo; Min Zhong; Qiujun Ruan; Yizhong Huang; Changlei Guo; Huiying Xu; Kaijun Che; Bin Xu; Zhiping Cai (IEEE Photonics Journal, 2016)
We report the generation of tunable high-repetition-rate (0.1–1 THz) femtosecond pulses based on a quasi-continuous wave (CW) dual-pumped all-fiber cascaded four-wave-mixing (FWM) scheme without requiring a cavity resonator. By synchronously injecting two pulse-modulated lasers into an 85-m-long dispersion-flat highly nonlinear fiber, cascaded FWM processes under only ∼30-mW average pump power are efficiently initiated to form the Kerr frequency combs near 1.56 $μ\text{m}$ . Phase locking of the Kerr combs is confirmed by real-time measurements using an autocorrelator, and stable ultrashort pulse trains are observed. The pulse repetition rate can be tuned continuously in the range of 0.1∼1 THz by controlling the wavelength spacing between the two pump lasers. The pulse duration can be correspondingly adjusted from 1.66 ps to 262 fs. Such quasi-CW dual-pumped all-fiber cascaded-FWM frequency combs with the advantages of compactness and flexibility could provide a practical solution for generating ultrahigh-repetition-rate femtosecond pulses.